Clinical practice in Portuguese sexology - Alarcão, V.; Ribeiro, S.; Almeida, J.; Giami, A. (Journal of Sex and Marital Therapy, 2017)
Few studies explore the clinicians' knowledge, attitudes, and practices regarding sexuality, despite their role in the sexual-health socialization process. This study focuses on Portuguese sexologists engaged in clinical practice. It aims to characterize sexologists' sex education and training and their clinical practices, including diagnostic and therapeutic approaches. This research followed the methodology of an European survey on sexology as a profession (Euro-Sexo). From the 91 respondents who completed questionnaires, 51 (56%) were active in clinical practice. Results indicate that the Portuguese clinical sexologist is significantly older, predominantly male, has had training in sexology, performs more scientific research, and is more engaged in teaching activities when compared to nonclinical working sexologists. This article describes the main sexual problems presented by patients to Portuguese clinical sexologists and highlights differences in the professional groups and approaches toward treating these problems by medical doctors and nonmedical professionals. Results reinforce the idea that there are intra-European differences in the educational background of sexologists and reveal important variations in Portuguese sexologists' education, training, and clinical practice. The representations and practices of the sexologists in Portugal, as in other European countries, are embedded in cultural scenarios and sexual cultures, with implications for the clinical practice.